2018
DOI: 10.1159/000491693
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Non-Invasive Auricular Acupressure for Treating Constipation in Leukemia Patients Undergoing Chemotherapy: A Systematic Review

Abstract: Background: The aim of this systematic review was to evaluate the available evidence from randomized controlled trials (RCTs) of auricular acupressure (AA) therapy for preventing constipation in leukemia patients undergoing chemotherapy. Methods: We searched 5 English databases and 4 Chinese databases, from their inception until August 2017. Quantitative syntheses of RCTs were conducted using RevMan 5.3 software. Study selection, data extraction, and validation were performed independently by 2 reviewers. Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Therefore, auricular acupuncture is easier to implement in clinical settings than body acupuncture. In oncology, auricular therapy has been studiedespecially in the treatment of cancer-related pain, but also for constipation-and appears to be effective and safe [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, auricular acupuncture is easier to implement in clinical settings than body acupuncture. In oncology, auricular therapy has been studiedespecially in the treatment of cancer-related pain, but also for constipation-and appears to be effective and safe [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In another review study, Chen et al (2018) reviewed 5 clinical trials that used AA in the treatment and prevention of constipation in leukemia patients undergoing chemotherapy. They reported AA can improve constipation and its associated quality of life [ 36 ]. Similar to present study, the study by Yang et al (2014) investigating the effectiveness of AA in patients with opium-induced constipation reported that AA had a positive effect on constipation-related quality of life [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that this therapy is contemplated by the Nursing Interventions Classification in a nursing intervention called "Acupressure" (15) , and has been the target of investigations in clinical nursing practice. Among some examples, one can mention the improvement in quality of life (16) , nausea/vomiting control (17) and constipation in cancer patients (18) , and even as non-pharmacological therapy to control pain in certain clinical conditions, such as chronic pain in the spine (19) and labor (20) .…”
Section: Introductionmentioning
confidence: 99%